Visual Recontextualization Maintains Narrative Integrity Amidst Visual Change in Photo Essay Works: Rekontekstualisasi Visual Memertahankan Integritas Naratif Di Tengah Perubahan Visual Dalam Karya Foto Esai - Handry Rochmad Dwi Happy; Yogi Widya Saka Warsaa; Elfa Olivia Verdiana (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This article discusses visual recontextualization in essay photography with the aim of understanding how visual symbols from various cultural and historical contexts can strengthen visual narratives. Through a semiotic approach, this study shows that essay photos do not only represent what is seen on the surface, but also convey deeper meanings through symbolism and interpretative processes. The findings demonstrate the importance of visual literacy for viewers in interpreting meanings that go beyond visual appearance. The process of recontextualization facilitates the enjoyment of richer emotional and intellectual experiences, making essay photos both documentary and reflective. This study also underlines the need for a deeper understanding of visual signs and symbols in creating meaning, as well as the challenges faced by photographers and viewers in understanding complex layers of meaning. Implications of this study include the need to strengthen visual literacy in the context of photography making and appreciation, as well as recommendations for further research in the fields of semiotics and visual arts